Alternatif Pengembangan Pengelolaan Hutan Bersama Masyarakat pada Lembaga Masyarakat Desa Hutan KPH Cepu - Asti Istiqomah; Helena Safira Dwisela (Institut Pertanian Bogor, 2022)
Community Forest Management (PHBM) in KPH Cepu was initiated in 2002 with the involvement of the Wana Amerta Forest Village Community Institution (LMDH). Management involvement is not only in the use of the area for intercropping agriculture but also in nature tourism. However, nature tourism management is not optimal due to limited access, facilities, and attractions. This study aims to identify a management system, estimate the economic benefits of PHBM LMDH Wana Amerta and analyze the potential development of nature tourism in Kedungpupur at LMDH Wana Amerta. The methods used were the descriptive method, income analysis, and the contingent valuation method. The results show that the PHBM management system uses a profit-sharing system. Profit-sharing varies based on the type of utilization where the agreement is contained in the Cooperation Agreement. Total economic benefits for the community from PHBM is IDR12,907,551,780/year, where the most significant benefit (99.51%) is from non-timber forest products, and the rest is from tourism services. The overall value of PHBM benefits can meet 70.72% of household expenditure needs. The utilization of nature tourism services is prospective to be developed to increase the economic benefits of CBFM. If the facilities are improved, photo spots and outbound attractions are provided, tourists are willing to pay a tourist fare from IDR5,000 to IDR26,563. Keywords: nature tourism services, LMDH, economic benefits, PHBM, willingness to pay